The role transition of radiotherapy for the treatment of liver cancer in the COVID-19 era - Li, Zheng; Hu, Yue; Zeng, Ming; Hu, Qinyong; Ye, Fei; Liu, Ruifeng; Cai, Hongyi; Li, Qiang; Wang, Xiaohu (Frontiers in Oncology, 2022)
The uncontrollable COVID-19 crises in the SARS-CoV-2 high-prevalence areas have greatly disrupted the routine treatment of liver cancer and triggered a role transformation of radiotherapy for liver cancer. The weight of radiotherapy in the treatment algorithm for liver cancer has been enlarged by the COVID-19 pandemic, which is helpful for the optimal risk-benefit profile.